Biorreguladores como auxiliar en el proceso fisiológico en la fecundación de naranjilla común (Solanumquitoense Lam.) - Romero Pérez, Daniel Eduardo (2012)
The use of bioregulators has given excellent results in a number of crops, obtaining quality fruits, increases in yield per hectare and therefore greater profitability. This research work was conducted in the north west of the province of Pichincha at the "Santa Maria" ow ned by Mr. Daniel Romero, located in the San Miguel by the Banks to 740 meters above sea level, was evaluated in this research as an assistant in the bio-physiological process common naranjilla fertilization (Solanum quitoense Lam.) and the following objectives a) evaluate the effect of bioregulators as an assistant in the physiological process of fertilization in common naranjilla (Solanum quitoense Lam.), b) determine the efficiency of the bio-physiological process naranjilla fruit set in common c) Analyze economic performance of the treatments under study Experiment design was employed randomized complete block to determine the statistical difference between means we applied the multiple range test of Tukey. The variables evaluated were: number of flowers per inflorescence, number of flowers pollinated at 20, 25 and 30 days percentage of fertilized fruits at 30 and 40 days, the days that elapsed until harvest, fruit weight diameter fruit, yield per plot and per hectare per treatment and utility costs The results of the bio as an assistant in the physiological process of fertilization in common naranjilla (Solanum quitoense Lam), it follows that if there were significant differences among treatments, the percentage of fruit setbetween treatments, which showed greater efficiency was the Maxi-growexcel T1 400ml/ha-1 with 58.41% and the lowest average recorded by the T4 treatment absolute Witness 43.47% respectively. The greater weight and diameter of fruits was achieved with the application of Maxi-growexcel with a weight of 156.35 g and 7.60 cm average diameter and lower weight recorded with absolute control T4 146.28g and a diameter of6.88 cm, the harvest season, showed no statistically significant difference between treatments, the treatment reported less time to reap what Ergostin registered 300 ml/ ha-1, 243.50 days, the treatment took longer T4 harvest absolute control with 254.75 days. Productivity performance is more efficient Maxi-growexcel treatment with kg/ha-1 20.742,25 and treatment occurred less average absolute Witness Kg/ha-1 18047.25 respectively, the economic analysis of the treatments, most cost effective treatment is the treatment Maxi-growexcel 400ml / ha-1.